Finite-temperature gluon spectral functions from Nf=2+1+1 lattice QCD - Ilgenfritz, Ernst-Michael; Pawlowski, Jan M.; Rothkopf, Alexander (The European physical journal. C, Particles and fields, 2018)
We investigate gluon correlation functions and spectral functions at finite temperature in Landau gauge on lattice QCD ensembles with Nf=2+1+1Nf=2+1+1N_f=2+1+1 dynamical twisted-mass quarks flavors, generated by the tmfT collaboration. They cover a temperature range from 0.8≤T/TC≤40.8≤T/TC≤40.8\le T/T_C\le 4 using the fixed-scale approach. Our study of spectral properties is based on a novel Bayesian approach for the extraction of non-positive-definite spectral functions. For each binned spatial momentum we take into account the gluon correlation functions at all available discrete imaginary frequencies. Clear indications for the existence of a well defined quasi-particle peak are obtained. Due to a relatively small number of imaginary frequencies available, we focus on the momentum and temperature dependence of the position of this spectral feature. The corresponding dispersion relation reveals different in-medium masses for longitudinal and transversal gluons at high temperatures, qualitatively consistent with weak coupling expectations.